The Role and Activities of the Hellenic Red Cross During the First Five Years of the Economic Crisis in Greece (2010-2014)—A Retrospective Study - Tagarakis, Ioannis; Tagarakis, Georgios (International Journal of Social Science Research, 2024)
Aim. To investigate the contribution of the Hellenic Red Cross to the Greek Society during the first five and more severe years (2010-2014) of the profound financial crisis in Greece. Material And Methods. We retrospectively investigated the actions and contribution of the Hellenic Red Cross for the aforementioned five-year period. The research material was accumulated by research in the Internet, the archives, and the official webpage of the Hellenic Red Cross (Google, official web page of the ICRC and IFRC), from the Hellenic Ministry of Health and the Hellenic Ministry of Immigration and Asylum. Results. A huge amount of over 247 actions were detected for the research period. More than 17,708 people were examined and treated from the specialized medical personnel of the Hellenic Red Cross and 3,266 individuals were trained in basic first aid and hygiene. The final amount of 297,757€ were donated and 5,880 welfare packages were delivered. Conclusions. The current study has concluded that the contribution of the Hellenic Red Cross to the Greek society during the most severe phase of the recent financial crisis was outstanding and consists an example for any other Non-Governmental, Non for Profit Organizations in the future.